Quality of Fish Sold at Traditional Markets in Tobelo City - Akerina, Febrina Olivia (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The waters of North Halmahera are a fishing area with abundant potential of small pelagic fish. Fishermen in Tobelo use a mini purse seine fishing gear which in local terms is called pajeko. The catch of pajeko fishermen is dominated by Mackarel tuna and Mackerel scad. The aim of this study was to determine the quality of fish caught by fishermen who are sold in one of the markets in Tobelo through organoleptic and pH analysis. Samples were taken randomly and analyzed descriptively so that the data were presented in the form of figures and tables. The results of the average pH analysis ranged from 6.00 - 6.50 and the results of the organoleptic analysis showed that the value was above 7 which indicated that the fish was still fresh.